Hepato-Protective Potentials of Formulated Purple Fleshed Potato-Soybean and Peels of Purple Fleshed Potato-Soybean (Solanum Tuberosum) Based Diets on Wistar Rats Induced with Trypanosomiasis - John, Abigail Evans; Isong, Nkoyo B.; Mbagwu, Herbert O. C.; Udoh, Mfoniso E. (American Journal of Biomedicine and Pharmacy, 2025)
The study evaluates the protective potential of formulated purple fleshed potato-soybean diets on Trypanosomiasis induced hepatotoxicity in wistar rats. The inadequacy of chemotherapy in in curing Trypanosomiasis and other dysfunctions caused by synthetic drugs is enough reason to formulate and evaluate some diets hepa-protection effect. The coded diets PFP1SJC3G2, PFP1SJC3G2 and PFP3SJC3G2 were formulations for HAT while PPL4SJC3G2 for AAT. Forty-Two animals were randomly divided into seven (7) groups (non-infected fed with rat pellet, infected fed with rat pellet only, infected treated with formulated diet PFP1SJC3G2 only, infected treated with PFP2SJC3G2 diet, infected treated with PFP3SJC3G2 diet, infected treated with PPL4SJC3G2 diet and infected treated with drug) of six rats each. The diets were administered once daily and drugs once in the cause of the experiment. AST, ALP and ALT level were returned to normal and showing that the effects of the formulated diets to the liver function are dose dependent and higher dose administration seems to be safe than the lower dose. The study demonstrated that the diets could ameliorate or reverse liver damage induced by Trypanosomiasis in wistai rats.